Augustine - Matthews, Gareth B., 1929- (Malden, Mass. : Blackwell Pub., 2005)
"This survey takes readers on a thought-provoking tour through the life and work of Augustine. Topics discussed include skepticism, language acquisition, mind-body dualism, philosophical dream problems, time and creation, faith and reason, foreknowledge and free will. The book concludes with a consideration of how Augustine could be both a religious believer - indeed, a prominent theological dogmatist - and also a Socratic philosopher."--BOOK JACKET.
The first-person point of view -- Augustine's life -- Skepticism -- Language -- The Augustinian cogito -- Mind--body dualism -- The problem of other minds -- Philosophical dream problems -- Time and creation -- Faith and reason -- Foreknowledge and free will -- The problem of evil -- Wanting bad things -- Lying -- Happiness.
Includes bibliographical references and index.
Keywords: Augustine, -- Saint, Bishop of Hippo